A METHODOLOGY TO STUDY PEDAGOGICAL EDUCATION OF UKRAINE: THE REGIONAL DIMENSION - Zuziak, Tetiana; Lavrinenko, Oleksandr; Marushchak, Oksana; Semenovska, Larysa; Klochko, Oksana (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2021)
Aim of the research is to validate the methodological approaches, developed by the authors, for the further use in the studies on historical pedagogy that within the regional aspect examine the processes of emergence of pedagogical education in Ukraine. For highlighting the issues of methodology of the historical and pedagogical research within the regional dimension, contemporary scientific approaches were used, including the integrated, systematic, activity, and synergic ones. The principles of objectivity, evidence, comprehensiveness, substantive analysis, of historical and logical coherence, of continuity, and systematic one were chosen as the main methodological grounds for the research. The study is novel in that it allows to assert: the mentioned methods of research with regard to its key concepts provide an opportunity to compare and trace the evolution and dynamics of development of the pedagogical education of the region within the defined chronological frame, shaping it as a complex, controversial process, influenced by many factors. The results prove that a research on pedagogical history should be grounded in holistic, historical and chronological, systematic, paradigm, structural, functional, axiological, and cultural studies approaches, be science-based, historically accurate, congruous with nature and culture. Within the scope of these approaches and principles, appropriate research methods should be used, i.e. empirical, general-science and specialized ones.